Surgical management of AAST grades III-V hepatic trauma by Damage control surgery with perihepatic packing and Definitive hepatic repair–single centre experience - Doklestić, Krstina (World J Emerg Surg, 2015)
BACKGROUND: Severe liver injury in trauma patients still accounts for significant morbidity and mortality. Operative techniques in liver trauma are some of the most challenging. They include the broad and complex area, from damage control to liver resection. MATERIAL AND METHOD: This is a retrospective study of 121 trauma patients with hepatic trauma American Association for Surgery of Trauma (AAST) grade III–V who have undergone surgery. Indications for surgery include refractory hypotension not responding to resuscitation due to uncontrolled hemorrhage from liver trauma; massive hemoperitonem on Focused assessment by ultrasound for trauma (FAST) and/or Diagnostic peritoneal lavage (DPL) as well as Multislice Computed Tomography (MSCT) findings of the severe liver injury and major vascular injuries with active bleeding. RESULTS: Non-survivors have significantly higher AAST grade of liver injury and higher Injury Severity Score (ISS) (p = 0.000; p = 0.0001). Non-survivors have significant hypotension on arrival and lower Glasgow Coma Scale (GCS) on admission (p = 0.000; p = 0.0001). Definitive hepatic repair was performed in 62(51.2 %) patient. Damage Control, liver packing and planned re-laparotomy after 48 h were used in 59(48.8 %). There was no statistically significant difference in terms of the surgical approach. There was significant difference in the amount of red blood cells (RBC) transfusion in the first 24 h between survivors and non-survivors (p = 0.001). Overall mortality rate was 33.1 %. Regarding complications non-survivors had significantly prolonged bleeding and higher rate of Acute respiratory distress syndrome (ARDS) (p = 0.0001; p = 0.0001), while survivors had significantly higher rate of pleural effusion (p = 0.0001). CONCLUSION: All efforts in the treatment of severe liver injuries should be directed to the rapid and effective control of bleeding, because uncontrollable hemorrhage is the cause of early death and it requires massive blood transfusion, all of which contributes to the late fatal complication.